Nutrition Literacy Proportion Differences among Regular Undergraduate Students in Universitas Indonesia Year 2021 - Deasy Andesbrenta Sadikin (Amerta Nutrition, 2021)
Background: Nutrition literacy is the ability to obtain, process, understand, and use nutritional and dietary information, as well as access to the services needed to make good nutritional decisions. Low nutritional literacy can have an impact on a poor diet and lead to the incidence of non-communicable diseases related to nutrition, such as diabetes, obesity, and hypertension. College students are prone to develop poor eating habits if not supported by good nutrition literacy.Objectives: This study measured the difference in the proportion of nutritional literacy in regular active undergraduate students at the University of Indonesia based on the cluster of science, gender, paternal and maternal education level, pocket money, and media use.Methods: The study design used is a cross-sectional design with quota sampling method to get 130 samples of students from Health Science Cluster and 130 samples of students from Non-Health Science Cluster.Results: The results of this study showed that the majority of the University of Indonesia students in 2021 has an adequate level of nutrition literacy (62.7%). The results of the bivariate analysis also showed a significant difference in proportion to the level of total nutrition literacy based on cluster of science (OR = 6.7, p-value < 0.01), gender (OR = 2.25, p-value < 0.01), and media use (OR = 4.36, p-value < 0.01). In addition to these factors, there was also a difference in proportion between the level of interactive nutrition literacy based on maternal education level (p-value < 0.05)Conclusions: Students from non-health science cluster are at risk of having a lower level of nutrition literacy compared to students from health science cluster. There are differences in the proportion of nutritional literacy levels based on cluster of science, gender, maternal education level, and media use.